Sustainable Agriculture in Kansas - Janke, Rhonda; Kok, Hans; Fjell, Dale L. (My University, 1998)
This publication provides an introduction to sustainable agriculture in Kansas.
MF2263_1998_01
Keywords: MF2263; Environment and Natural Resources; Livestock; Economics; MF